(x+5)^3-3=-67 11-(2x-3)^2=2

Question

(x+5)^3-3=-67
11-(2x-3)^2=2

in progress 0
Doris 1 year 2020-11-27T03:09:46+00:00 2 Answers 41 views 0

Answers ( )

    0
    2020-11-27T03:10:46+00:00

    Giải thích các bước giải:

     a) $(x+5)^3-3=-67$
    $=>(x+5)^3=-64$
    $=>x+5=-4$
    $=>x=-9$
     b) $11-(2x-3)^2=2$
    $=>(2x-3)^2=9$
    Th1: $2x-3=3$
    $=>2x=6$
    $=>x=3$
    Th2: $2x-3=-3$
    $=>2x=0$
    $=>x=0$

    0
    2020-11-27T03:11:18+00:00

    Đáp án:

    $(x + 5)³ – 3 = – 67$

    $⇔ (x + 5)³ = – 67 + 3$

    $⇔ (x + 5)³ = – 64$

    $⇔ (x + 5)³ = ( – 4)³$

    $⇔ x + 5 = – 4$

    $⇔ x = – 9$

    $11 – (2x – 3)² = 2$

    $⇔ (2x – 3)² = 11 – 2$

    $⇔ (2x – 3)² = 9$

    $⇔$ \(\left[ \begin{array}{l}(2x-3)²=3²\\(2x-3)² = (-3)²\end{array} \right.\) 

    $⇔$ \(\left[ \begin{array}{l}2x-3=3\\2x-3=-3\end{array} \right.\) 

    $⇔$ \(\left[ \begin{array}{l}x=3\\x=0\end{array} \right.\) 

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )